Comparison of bovine and mouse pituitary glycoprotein hormone pre-α subunits synthesized in vitro - Giudice, Linda C. (1979)
Poly(A)-containing RNA isolated from bovine and mouse pituitaries and a mouse pituitary thyrotropic tumor was translated in a wheat germ cell-free biosynthetic system. A precursor of the glycoprotein hormone α subunit, “pre-α,” was immunoprecipitated from the translation mixtures with antiserum against bovine luteinizing hormone (LH; lutropin) α. The specificity of the immunoprecipitation was shown by competition with authentic bovine LHα and lack of competition with bovine thyroid-stimulating hormone (TSH; thyrotropin) β. Bovine and mouse pre-α subunits migrated identically in sodium dodecyl sulfate gradient polyacrylamide slab gels with an apparent molecular weight of about 17,000. Pre-α comprised 2-3% and 20-30% of the total proteins translated with pituitary and pituitary tumor mRNA, respectively. Microanalysis of amino acid sequence of the pre-α subunits containing various radiolabeled amino acids gave the following partial sequence for mouse tumor pre-α: [Formula: see text] Met was also found in positions 1, 14, and 17 in mouse pituitary pre-α but only in residue 1 of the bovine pituitary pre-α subunit. Leu was found in identical positions in bovine pituitary pre-α, with an additional Leu in position 17. Leu in the common positions (12, 15, 19, and 22) has also been found in human choriogonadotropin pre-α subunit [Birken, S., Fetherston, J., Desmond, J., Canfield, R. & Boime, I. (1978) Biochem. Biophys. Res. Commun. 85, 1247-1253]. The data demonstrate that pituitary as well as placental glycoprotein hormone α subunits are synthesized with an amino-terminal hydrophobic extension, in accord with the “signal hypothesis” for secreted proteins. Furthermore, the positions of the hydrophobic amino acid Leu have been strictly conserved in pre-α subunits from various species and in two different tissues, the pituitary and placenta.